The need for occupational health services in Bloemfontein - P. P. du Rand; W. Schoeman (AOSIS, 2003)
The research was undertaken to ascertain the need for occupational health services in Bloemfontein with the possibility of planning such services in small and medium industries. As mentioned in the problem statement, small and medium industries generally do not employ an occupational health nurse. The survey method was used and the research was descriptive in nature. Questionnaires were used to collect information and the researcher evaluated the environment for safety hazards by means of a checklist. Three samples were conducted: a samples test to identify the industries and employees and goal-directed selection to identify the managers. The main findings of the research showed that managers and employees do not know about industrial health.